Naoxintong Retards Atherosclerosis by Inhibiting Foam Cell Formation Through Activating Pparα Pathway - Wang, Zeng; Shi, Huairui; Zhao, Huan; Dong, Zhen; Zhao, Buchang; Weng, Xinyu; Liu, Rongle; Li, Xiao; Hu, Kai; Zou, Yunzeng; Sun, Aijun; Ge, Junbo (Current Molecular Medicine, 2018)
Backgrounds: We recently reported that Naoxintong (NXT), a China Food and Drug Administration (FDA)-approved cardiac medicine, could reduce the plaque size, but the underlying mechanism remains elusive now. Objective: In this study, we investigated the effects of NXT on foam cell accumulation both in vivo and in vitro and explored related mechanisms. Method: THP-1 cells and bone marrow-derived macrophages were incubated with oxidized low-density lipoprotein (ox-LDL) with/without Naoxintong. ApoE-/- mice fed an atherogenic diet were administered to receive NXT for eight weeks. Macrophage-derived foam cell formation in plaques was measured by immunohistochemical staining. Expression of proteins was evaluated by Western blot. Lentivirus was used to knockdown PPARα in THP-1 cells. Results: After NXT treatment, foam cell accumulation was significantly reduced in atherosclerotic plaques. Further investigation revealed that oxidized low-density lipoprotein (ox-LDL) uptake was significantly decreased and expression of scavenger receptor class A (SR-A) and class B (SR-B and CD36) was significantly downregulated post-NXT treatment. On the other hand, NXT increased cholesterol efflux and upregulated ATP-binding cassette (ABC) transporters (ABCA-1 and ABCG-1) in macrophages. Above beneficial effects of NXT were partly abolished after lentiviral knockdown of PPARα. Conclusion: Our findings suggest that NXT could retard atherosclerosis by inhibiting foam cell formation through reducing ox-LDL uptake and enhancing cholesterol efflux and above beneficial effects are partly mediated through PPARα pathway.
Keywords: atherosclerosis